India - Pakistan Trade - Nisha Taneja (Indian Council for Research on International Economic Relations (ICRIER), 2006)
Quantitative studies estimate that potential two way trade between India and Pakistan can be about 10 times than its rather unsatisfactory current level of 613 million. Moving towards realizing this trade potential is clearly in the interest of both countries and the region. In this context this study identifies areas of trade and investment co-operation between the two countries. On the basis of a survey conducted in three cities viz., Delhi, Mumbai and Amritsar the paper examines the characteristics of firms engaged in Indo-Pakistan trade. It also estimates existing transport arrangement between the two countries and the impact of all extant non-tariff barriers. The study suggests that the most important step towards enhancing trade would be to adopt the MFN principle as the current policy inhibits trade, lacks transparency and leads to high transaction costs. The study finds that transportation links between the two countries are inadequate and suggests that new rail and road links should be opened. Transaction costs of trading between India and Pakistan are high and can be lowered by implementing some rather simple policy measures that are spelled out in the paper. The study also examines recent developments in BIMSTEC, ASEAN and in Indo-Sri Lanka and Indo-Nepal trade agreements, and draws lessons to enhance Indo-Pakistan trade.
Keywords: O53; L6; L8; F13; 330; South Asia; India-Pakistan trade; commercial policy; MFN; Internationale Wirtschaftsbeziehungen; Internationale Wirtschaft; Außenwirtschaftspolitik; Handelsliberalisierung; Indien; Pakistan